A música é uma linguagem?: um estudo sobre o discurso musical no contexto do século XX - Rinaldi, Arthur [UNESP] (2014)
The XXth-century Western Art Music has been the object of many studies, however, the widespread vision that this is an extremely plural repertoire tends to isolate the different aesthetical-compositional trends. If this perspective has allowed many advances regarding the knowledge of their particularities, it also has hindered the comprehension of their similarities and confluences. Particularly important is the fact that contemporary musical compositions, regardless of the trends they are associated with, are the product of compositional strategies that aim to establish some kind of dialogue with the listeners, from the concert hall public to the professional theorist/analyst. The starting point for this dialogue is the constitution of a qualitative leap, where the different sound materials are perceived as integrating a larger and more complex unity, the musical composition, which is only possible if it is established come correlation between the formal organization of the composition and the interpretative capacities of the listener. It is up to the fields of Musical Theory and Analysis to ponder upon this matter, nonetheless they are themselves as complex as the contemporary musical plurality they try to comprehend: nowadays, there is a considerable diversity of analytical tools, which are based on distinct (even conflicting) theoretical grounds. Against this seeming frame of total relativity regarding the possibilities of comprehension of the contemporary musical repertoire, it is proposed here that there are patterns of musical organization that transcend the stylistic differences, which can be grasped from the perspective that music is a language. This thesis is supported by the discussion of a group of central tenets: 1) that the processes of musical listening and musical analysis are directly dependant of a system of categorization structured around our perceptual and cognitive mechanisms ...